The Development of educational materials in Arabic Writing Lesson at Babussalam Islamic Boarding School - Umi Mahmudah; Yuangga Kurnia Yahya (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Teaching material is an important aspect for teaching and learning activities, In babusasalam boarding school teaching material for writing skills is very needed. All students must be able to write Arabic language properly and correctly, but the fact there are many student can't to write it properly. This happened, because the teaching and learning activities in Arabic Writing lesson did not have any teaching materials relevant to student needs. Therefore, the researcher wants to developing teaching materials on Arabic Writting lesson with the aim teaching material be able to be reference for the teacher. In this study, researchers used Research and Development theory. For data collection, the method using are : observation, interviews, documentation, trials and test. The results from post-test and pre-test showed that the teaching material is effective for teaching arabic writing lesson. The development of teaching materials is carried out in the following stages; 1) preliminary study, 2) planning and developing material, 3) validity of experts, 4) specification of material objectives and teaching steps 5) design of teaching materials 6) Validity Test.